Regional Inequality in Morocco: A Bibliometric Analysis of AI and Education as Drivers for Reducing Inequality - El houssin Ouassou; Boutaina Ismaili Idrissi (African Scientific Journal, 2025)
Abstract The current research presents a bibliometric analysis of emerging methodologies applied to the study of regional inequality in Morocco, with particular emphasis on artificial intelligence (AI), remote sensing, and education. Using bibliographic data collected from Scopus and Web of Science, the study maps the intellectual structure of the field by analyzing publication trends, citation networks, influential authors, and evolving thematic clusters. The findings reveal a notable global shift toward the adoption of advanced computational tools—such as machine learning, deep learning, big data analytics, and geospatial technologies—for monitoring and analyzing spatial disparities. However, Moroccan academic contributions remain relatively limited within this rapidly evolving research domain. A key insight emerging from the analysis is the increasing integration of education as a critical variable in spatial inequality research. Unequal access to quality education, particularly in rural and marginalized areas, is widely recognized as a major factor sustaining territorial divides. Conversely, innovative educational strategies—including digital learning platforms, vocational training, and lifelong education—are frequently identified as mechanisms for fostering regional convergence and inclusive development. This bibliometric mapping underscores the growing recognition of interdisciplinary approaches that combine technological innovation with social policy insights. It calls attention to the urgent need for Morocco to enhance its research capacity and policy design through greater investment in AI-driven, education-focused strategies. By identifying existing gaps and emerging opportunities, this study offers a methodological foundation for future research and policymaking aimed at promoting spatial equity and territorial cohesion in Morocco and comparable settings. Keywords: Regional Inequality, Education, Artificial Intelligence, Morocco, Bibliometric